Role of Phosphorylated Gonadotropin-Regulated Testicular RNA Helicase (GRTH/DDX25) in the Regulation of Germ Cell Specific mRNAs in Chromatoid Bodies During Spermatogenesis - Anbazhagan, Rajakumar; Kavarthapu, Raghuveer; Coon, Steven L.; Dufau, Maria L. (Frontiers in Cell and Developmental Biology, 2020)
GRTH/DDX25 is a member of the DEAD-box family of RNA helicases that play an essential role in spermatogenesis. GRTH knock-in (KI) mice with the human mutant GRTH gene (R242H) show loss of the phospho-species from cytoplasm with preservation of the non-phospho form in the cytoplasm and nucleus. GRTH KI mice are sterile and lack elongated spermatids and spermatozoa, with spermatogenic arrest at step 8 of round spermatids which contain chromatoid body (CB) markedly reduced in size. We observed an absence of phospho-GRTH in CB of GRTH KI mice. RNA-Seq analysis of mRNA isolated from CB revealed that 1,421 genes show differential abundance, of which 947 genes showed a decrease in abundance and 474 genes showed an increase in abundance in GRTH KI mice. The transcripts related to spermatid development, differentiation, and chromatin remodeling (Tnp1/2, Prm1/2/3, Spem1/2, Tssk 2/3/6, Grth, tAce, and Upf2) were reduced, and the transcripts encoding for factors involved in RNA transport, regulation, and surveillance and transcriptional and translational regulation (Eef1a1, Ppp1cc, Pabpc1, Ybx3, Tent5b, H2al1m, Dctn2, and Dync1h1) were increased in the CB of KI mice and were further validated by qPCR. In the round spermatids of wild-type mice, mRNAs of Tnp2, Prm2, and Grth were abundantly co-localized with MVH protein in the CB, while in GRTH KI mice these were minimally present. In addition, GRTH binding to Tnp1/2, Prm1/2, Grth, and Tssk6 mRNAs was found to be markedly decreased in KI. These results demonstrate the importance of phospho-GRTH in the maintenance of the structure of CB and its role in the storage and stability of germ cell-specific mRNAs during spermiogenesis.